1999
DOI: 10.1590/s0100-879x1999001000007
|View full text |Cite
|
Sign up to set email alerts
|

Zinc and water intake in rats: investigation of adrenergic and opiatergic central mechanisms

Abstract: We have demonstrated that central administration of zinc in minute amounts induces a significant antidipsogenic action in dehydrated rats as well as in rats under central cholinergic and angiotensinergic stimulation. Here we show that acute third ventricle injections of zinc also block water intake induced by central ß-adrenergic stimulation in Wistar rats (190-250 g). Central inhibition of opioid pathways by naloxone reverses the zinc-induced antidipsogenic effect in dehydrated rats. After 120 min, rats recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 12 publications
1
9
0
Order By: Relevance
“…Indeed, a result of water deprivation is change to hair coat and hair loss (57,58), and consequently, the reported drop in daily water intake might be in part responsible for anagen retardation observed by us. On the other hand, it should still be considered a direct effect of zinc, which likely acts on the hypothalamic level as an antidipsogenic factor (59) and does not lead to a systemic stress response. It is particularly difficult to assess in in vivo experiments to what extent anagen inhibition is a result of direct zinc action on HFs, and to what extent – a result of antidipsogenic action of zinc.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, a result of water deprivation is change to hair coat and hair loss (57,58), and consequently, the reported drop in daily water intake might be in part responsible for anagen retardation observed by us. On the other hand, it should still be considered a direct effect of zinc, which likely acts on the hypothalamic level as an antidipsogenic factor (59) and does not lead to a systemic stress response. It is particularly difficult to assess in in vivo experiments to what extent anagen inhibition is a result of direct zinc action on HFs, and to what extent – a result of antidipsogenic action of zinc.…”
Section: Discussionmentioning
confidence: 99%
“…As the experimental animals were given zinc solution ad libitum , artificial water shortage to the level of the daily intake of zinc‐treated groups would cause the real water‐deprivation stress in control animals. Meanwhile, application of antidipsogenic factors, such as moxonidine (60) or zinc (59), can prevent water intake even in water‐deprived and dehydrated animals. It means that zinc may even cause a partial and temporal dehydration without actual water‐deprivation stress.…”
Section: Discussionmentioning
confidence: 99%
“…Zinc, a divalent cation with manifold biochemical and physiological functions, may play principal neuromodulatory roles in the central nervous system. Indeed, zinc is co-released with glutamate, and it modulates glutamatergic excitation by inhibiting N-methyl-D-aspartate (NMDA) receptors, and averts gammaaminobutyric acid (GABA) inhibition by blocking GABA-A receptor function [30,31] reported that zinc exerts its antioxidant property in ameliorating the effect of chlorpyrifos-induced erythrocyte fragility in Wistar rats. Neuropsychological performance has been reported to improve with Zn supplementation in young Chinese children, especially when other micronutrient nutrition is sufficient [27,28].…”
Section: Insights In Biomedicine Issn 2572-5610mentioning
confidence: 99%
“…They also showed that dehydrated rats under central cholinergic and angiotensinergic stimulation experienced antidipsogenic response to zinc treatment [25]. Further studies by this group demonstrated that zinc induced blockade of water intake in dehydrated rats may be, at least in part, due to stimulation of central opioid peptides [26].…”
Section: Reduction Of Water Intake By Zinc Acetatementioning
confidence: 99%
“…It was also shown that the inhibitory effect of zinc on water intake might be opioid-dependent. [26].…”
Section: Reduction Of Water Intake By Zinc Acetatementioning
confidence: 99%